1993
DOI: 10.1016/0014-5793(93)80184-v
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester as a lipoxygenase inhibitor with antioxidant properties

Abstract: Caffeic acid phenethyl ester, an active component of propolis extract, inhibits Yipoxygenase in the micromolar concentration range. The inhibition is of an uncompetitive type, i.e. the inhibitor binds to the enzyme-substrate complex but not to the free enzyme. Caffeic acid phenethyl ester also exhibits antioxidant properties. At a concentration of 10 PM, it completely blocks production of reactive oxygen species in human neutrophils and the xanthinelxanthine oxidase system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
315
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(322 citation statements)
references
References 14 publications
4
315
0
3
Order By: Relevance
“…Second, direct evidence for the relevance of 5-lipoxygenase activity in our systems is provided by the ability of 5-HETE to induce PCD in the same cell types ( Figure 2B). Third, the general lipoxygenase inhibitor NDGA (Ford-Hutchinson et al, 1994) and the more selective 5-lipoxygenase inhibitor caffeic acid (Ford-Hutchinson et al, 1994;Sud'ina et al, 1993;Tang et al, 1996) protected from H 2 O 2 -induced PCD to a similar extent ( Table 3), suggesting that activation of 5-lipoxygenase, but not other isoenzymes, occurs during apoptosis. NDGA is also a radical scavenger, but its radical scavenging ability is unable to protect human cells against ROS-induced death (O'Donnell et al, 1995;Tang et al, 1996).…”
Section: -Lipoxygenase Involvement In Apoptosis M Maccarrone Et Almentioning
confidence: 88%
See 1 more Smart Citation
“…Second, direct evidence for the relevance of 5-lipoxygenase activity in our systems is provided by the ability of 5-HETE to induce PCD in the same cell types ( Figure 2B). Third, the general lipoxygenase inhibitor NDGA (Ford-Hutchinson et al, 1994) and the more selective 5-lipoxygenase inhibitor caffeic acid (Ford-Hutchinson et al, 1994;Sud'ina et al, 1993;Tang et al, 1996) protected from H 2 O 2 -induced PCD to a similar extent ( Table 3), suggesting that activation of 5-lipoxygenase, but not other isoenzymes, occurs during apoptosis. NDGA is also a radical scavenger, but its radical scavenging ability is unable to protect human cells against ROS-induced death (O'Donnell et al, 1995;Tang et al, 1996).…”
Section: -Lipoxygenase Involvement In Apoptosis M Maccarrone Et Almentioning
confidence: 88%
“…Cell death induced by 5-HETE was associated with the DNA ladders typical of apoptosis, both in K562 cells (Figure 2B,inset) and in the other cell types (not shown). Conversely, the general lipoxygenase inhibitor NDGA (Ford-Hutchinson et al, 1994) and the selective 5-lipoxygenase inhibitor caffeic acid (Ford-Hutchinson et al, 1994;Sud'ina et al, 1993;Tang et al, 1996) significantly protected the different tumour cells from H 2 O 2 -induced PCD. Indeed, the addition of either 40 mM NDGA or 40 mM caffeic acid to the culture medium, together with H 2 O 2 , reduced the number of H 2 O 2 -induced apoptotic bodies by approximately 55 ± 60% (Table 3).…”
Section: Involvement Of 5-lipoxygenase In Pcdmentioning
confidence: 93%
“…It was suggested that CAPE altered the redox state of the cells and that CAPE-triggered apoptosis in Wt3A cells was associated with their reduced oxidant defences [15]. However, as we have shown previously, CAPE and DCHCU are antioxidants: they inhibit the production of reactive oxygen species (ROS) by human neutrophils and in a cell-free xanthinexanthine oxidase system to at least as great an extent as the other antioxidant LOX inhibitors, such as NDGA and caffeic acid [11,12]. It seems unlikely therefore that CAPE-and DCHCU-induced apoptosis can be explained simply as a result of the redox imbalance causing increased ROS production.…”
mentioning
confidence: 93%
“…Our previous investigations have shown that two lipophilic derivatives of caffeic acid, caffeic acid phenethyl ester (CAPE) and an intermediate in its chemical synthesis, N,N'-dicyclohexyl-O-(3,4-dihydroxycinnamoyl)-isourea (DCHCU) (see Scheme 1), are antioxidants which inhibit plant 5-and 15-lipoxygenases [11,12]. CAPE is a biologically active ingredient of honeybee propolis, a natural product which has been *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that caffeic acid inhibits both lipoxygenase activity and suppresses lipid peroxidation [10]. Caffeic acid completely blocks the production of reactive oxygen species (ROS) and xanthine/xanthine oxidase system [11].…”
Section: Introductionmentioning
confidence: 99%